Evaluation of Treatment with Omega-3 Fatty Acid Supplements on Salivary Levels of Resolvin E1 in Chronic Periodontitis Patients - Murali, Aparna C; Bhandary, Rahul; Ramesh, Amitha; Venugopalan, Geethu (Journal of Health and Allied Sciences NU, 2022)
Context Under healthy conditions, inflammation proceeds through natural healing processes by an organized cycle. Similar to any other systemic infection, periodontal disease is also a manifestation of dysregulated inflammatory pathway.Endogenous lipid mediators called resolvins and docosatrienes, produced from omega-3 fatty acid precursors, possess various immunoregulatory properties. These polyunsaturated fatty acids cannot be synthesized in body, instead these have to be taken through diet. This study aims to evaluate the effect of adjunctive treatment with daily dietary supplementation of omega-3 fatty acids in chronic periodontitis.Aims The aim of this study was to assess periodontal parameters and salivary levels of Resolvin E1 with and without dietary supplementation of omega-3 fatty acid capsules in chronic periodontitis patients.Methods and Materials Three-month comparative clinical study was performed on 52 patients allotted to two groups, each with 26 subjects. Both groups received an initial phase 1 therapy followed by additional dietary supplementation of 500 mg of omega-3 fatty acid capsules for 3 months for the test group. Salivary levels of Resolvin E1, periodontal parameters, including pocket probing depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), and periodontal inflamed surface area (PISA), were assessed at baseline, 1 and 3 months after the study.Statistical Analysis Used Data was analyzed with an unpaired t-test between the group and paired t-test for within the group comparison. p-Value less than 0.05 was considered significant.Results PPD and CAL showed statistically significant differences between the two groups and within the groups
Keywords: omega-3 Fatty acid supplements; PUFA; Resolvin E1; periodontitis